Syphilitic alopecia: uncommon trichoscopic findings - Linda Tognetti; Elisa Cinotti; Jean-Luc Perrot; Marco Campoli; Pietro Rubegni (Mattioli1885, 2017)
Syphilitic alopecia (SA) is considered an uncommon manifestation of secondary syphilis. SA can present in a diffuse form, resembling telogen effluvium, or in a moth-eaten form that mimics a variety of conditions (i.e., alopecia areata, trichotillomania, lichen planus pilaris or tinea capitis). When the two forms coexist, we observe a mixed pattern. Essential SA manifests without evidence of mucocutaneous syphilis manifestations and its diagnosis is often delayed. To date, trichoscopic description of SA forms are based on very few cases (i.e., five patients with moth-eaten SA and one with diffuse SA). This is the first report of a mixed pattern of essential SA: some new trichoscopic features-such as tapered bended hairs, erythematous background, diffuse scaling and perifollicular hyperkeratosis-are described in a 32-year-old man. In the absence of secondary syphilis manifestations, dermoscopy can be a useful tool that helps suspect and differentiate SA from its common mimickers.